Unique allergen-specific human IgE monoclonal antibodies derived from patients with allergic disease - Smith, Bryan R. E.; Reid Black, Kristina; Bermingham, Max; Agah, Sayeh; Glesner, Jill; Versteeg, Serge A.; van Ree, Ronald; Pena-Amelunxen, Glorismer; Aglas, Lorenz; Smith, Scott A.; Pomés, Anna; Chapman, Martin D. (Frontiers in Allergy, 2023)
Introduction Allergic reactions are mediated by human IgE antibodies that bind to and cross-link allergen molecules. The sites on allergens that are recognized by IgE antibodies have been difficult to investigate because of the paucity of IgE antibodies in a human serum. Here, we report the production of unique human IgE monoclonal antibodies to major inhaled allergens and food allergens that can be produced at scale in perpetuity. Materials and methods The IgE antibodies were derived from peripheral blood mononuclear cells of symptomatic allergic patients, mostly children aged 3–18 years, using hybridoma fusion technology. Total IgE and allergen-specific IgE was measured by ImmunoCAP. Their specificity was confirmed through ELISA and immunoblotting. Allergenic potency measurements were determined by ImmunoCAP inhibition. Biological activity was determined in vitro by comparing β-hexosaminidase release from a humanized rat basophilic cell line. Results Human IgE monoclonal antibodies (n = 33) were derived from 17 allergic patients with symptoms of allergic rhinitis, asthma, atopic dermatitis, food allergy, eosinophilic esophagitis, or red meat allergy. The antibodies were specific for five inhaled allergens, nine food allergens, and alpha-gal and had high levels of IgE (53,450–1,702,500 kU/L) with ratios of specific IgE to total IgE ranging from <0.01 to 1.39. Sigmoidal allergen binding curves were obtained through ELISA, with low limits of detection (<1 kU/L). Allergen specificity was confirmed through immunoblotting. Pairs of IgE monoclonal antibodies to Ara h 6 were identified that cross-linked after allergen stimulation and induced release of significant levels of β-hexosaminidase (35%–80%) from a humanized rat basophilic cell line. Conclusions Human IgE monoclonal antibodies are unique antibody molecules with potential applications in allergy diagnosis, allergen standardization, and identification of allergenic epitopes for the development of allergy therapeutics. The IgE antibody probes will enable the unequivocal localization and validation of allergenic epitopes.